Strengthening Tilapia Cultivation Through CBIB-Based Farming in Sigerongan Village, West Lombok Regency - Affandi, Rangga Idris; Abidin, Zaenal; Scabra, Andre Rachmat; Diniariwisan, Damai; Rahmadani, Thoy Batun Citra (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
Sigerongan Village in Lingsar District, West Lombok Regency, has quite large aquaculture potential, especially for tilapia commodities. However, in practice, farmers still face various obstacles such as low quality of maintenance management, sanitation, and feed use efficiency. Lack of understanding of Good Fish Farming Practices (CBIB) standards is one of the main factors that hinders increased productivity and sustainability of aquaculture businesses. This community service activity aims to improve the understanding and skills of tilapia farmers in Sigerongan Village in applying CBIB principles. Implementation methods include counseling, discussion, and direct assistance with a participatory and demonstrative approach. Evaluation is carried out to measure changes in participants' knowledge and attitudes before and after the activity. The results of the activity showed a significant increase in the understanding and technical skills of farmers related to aspects of biosecurity, water quality management, proper use of feed, and management of aquaculture waste. The participants also showed enthusiasm and commitment to implementing CBIB in their daily activities. This activity also encourages collective awareness of the importance of quality standards in sustainable aquaculture. In conclusion, CBIB training and mentoring have a positive impact on increasing the capacity of fish farmers in Sigerongan Village and have the potential to become a model for sustainable and competitive fisheries community empowerment.